PENGARUH WORD OF MOUTH, DISSATISFACTION, VARIETY SEEKING TERHADAP BRAND SWITCHING JASA KURIR J&T EXPRESS: (Studi Pada Pengguna Jasa Kurir Ekspedisi J&T Express di Kota Medan) - Anzala Sahru Ramadhan; Nicholas Marpaung (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The intense competition among courier service brands has led some consumers to choose to use J&T Express because it is considered better than other courier service brands. Factors that can influence this brand switching are word of mouth information from consumers, dissatisfaction, and the search for new variations. This study aims to analyze the influence of word of mouth on brand switching in J&T Express courier services, analyze the influence of dissatisfaction on brand switching in J&T Express courier services, analyze the influence of variety seeking on brand switching in J&T Express courier services, and the influence of word of mouth, dissatisfaction, and variety seeking on brand switching in J&T Express courier services. Sampling was done through probability sampling technique using 100 respondents as samples. The data analysis methods used are validity test, reliability test, classic assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that word of mouth, dissatisfaction, and variety seeking have a significant and simultaneous effect on brand switching.